Developing a framework for an undergraduate haematology curriculum in a Faculty of Health Sciences - Stefan, Daniela Cristina (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Curriculum Studies))--University of Stellenbosch, 2010.